Study of biochemical and haematological changes in football players - Tavares, Ana Sofia (2017)
Background - Football players develop throughout their practice, an endurance type exercise. This type of practice is known to cause changes both at the cellular level as well as on muscle enzymes. Modifications are also seen in terms of lipid profile, caused by the faster rate of metabolism of these molecules. The aim of this paper was to study the variation of biochemical and haematological parameters on football players. Methods - Blood samples were drawn from 18 football players undergoing an 8 hour-a-week training program. The following parameters were tested: lipid profile, creatine kinase (CK), lactate dehydrogenase (LDH), aspartate aminotransferase (AST); red blood cells (RBC) and their indices, haemoglobin and haematocrit. Results - The lipid profile showed that the HDL-Cholesterol mean (=53.33 mg/dL) was above the value determined as a target (37.00 mg/dL). The LDL-Cholesterol mean was below the target-value, as it was for the triglycerides. There were no significant differences between the real mean and the target value for total cholesterol. All creatine kinase (CK) values were above the target-value of 77 UI/L. The values obtained for lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) tests did not show any significant difference from targetvalues. No major differences from the target values were seen in terms of the haematological parameters. Conclusions - The results of this study have shown that the practice of physical exercise has caused a modification in the subject's lipid profile, especially on the HDL-C values. Concerning muscle enzymes, the only altered value found was for creatine kinase (CK). The so called sports anaemia was not confirmed.